Implementasi Nilai-nilai Kebhinekaan pada peserta didik di UPT SMA Negeri 7 Jeneponto - Sailan, Manan; Suyitno, Imam; Syam, Ayu Aprilia (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2024)
ABSTRACT This research aims to: (1) determine the strategies used by teachers in implementing diversity values at SMA Negeri 7 Jeneponto. (2) Knowing efforts to implement diversity values at UPT SMA Negeri 7 Jeneponto. (3) Knowing the inhibiting factors in implementing diversity values at UPT SMA Negeri 7 Jeneponto. This type of research is qualitative research with a descriptive approach. The sources of this research are Civics teachers and students. Data collection techniques are carried out through observation, interviews and documentation. Checking the validity of the data uses data source triangulation techniques.